Penerapan Metode SQ3RP pada Pembelajaran IPA untuk Meningkatkan Hasil Belajar Siswa - Sudirman Sudirman; Saemina Sarmina; Murniati Murniati; Ramsida Ramsida; Pahenra Pahenra (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2022)
The findings of the International Student Assessment (PISA) show that students' literacy skills, especially science or science in Indonesia, are categorized as low. Therefore, the purpose of this research is to improve student learning outcomes in physics subjects with the material concepts of elements, compounds, mixtures. This classroom action research applies the SQ3RP (Survey Question Read Recite Review and Practice) technique. The research subjects were students of class VII A of Junior High School (SMP) Negeri 2 Kendari, totaling 40 students. Collecting data using observation sheets and learning outcomes tests. The analysis used is descriptive analysis in the form of class averages and percentages and graph tables. The results showed that the increase in student learning outcomes using the SQ3RP method was very good because the pre-test results from 52.5% increased to 90.0% in the third cycle. While student learning activities have increased the average student activity at a degree of 80.0%.